Extraocular motoneuron pools develop along a dorsoventral axis in zebrafish, Danio rerio - Greaney, Marie R. (John Wiley and Sons Inc., 2016)

(untitled) (J Comp Neurol)
Both spatial and temporal cues determine the fate of immature neurons. A major challenge at the interface of developmental and systems neuroscience is to relate this spatiotemporal trajectory of maturation to circuit‐level functional organization. This study examined the development of two extraocular motor nuclei (nIII and nIV), structures in which a motoneuron's identity, or choice of muscle partner, defines its behavioral role. We used retro‐orbital dye fills, in combination with fluorescent markers for motoneuron location and birthdate, to probe spatial and temporal organization of the oculomotor (nIII) and trochlear (nIV) nuclei in the larval zebrafish. We describe a dorsoventral organization of the four nIII motoneuron pools, in which inferior and medial rectus motoneurons occupy dorsal nIII, while inferior oblique and superior rectus motoneurons occupy distinct divisions of ventral nIII. Dorsal nIII motoneurons are, moreover, born before motoneurons of ventral nIII and nIV. The order of neurogenesis can therefore account for the dorsoventral organization of nIII and may play a primary role in determining motoneuron identity. We propose that the temporal development of extraocular motoneurons plays a key role in assembling a functional oculomotor circuit. J. Comp. Neurol. 525:65–78, 2017. © 2016 The Authors The Journal of Comparative Neurology Published by Wiley Periodicals, Inc.